Мoral and axiological aspects in modern entrepreneurship studies - Boguslavskiy O.; Ignatovich N. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article deals with role and significance of moral and axiological aspects in modern economic studies. It bases the necessary and directions of entrepreneurship studies in the moral and axiological paradigm.